Iowa's forgotten general : Matthew Mark Trumbull and the Civil War - Lyftogt, Kenneth (Book collections on Project MUSE., 2007)
Matthew Mark Trumbull was a Londoner who immigrated at the age of twenty. Within ten years of his arrival in America, he had become a lawyer in Butler County, Iowa; two years later a member of the state legislature; and two years after that a captain in the Union Army. By the end of the Civil War, he was a brevet brigadier general, and in his later years he was an author and lecturer. Kenneth Lyftogt's biography details the amazing life of this remarkable man, also shedding light on the histories of the Third Iowa Volunteer Infantry and the Ninth Iowa Volunteer Cavalry.